Routing of the RAB6 secretory pathway towards the lysosome related organelle of melanocytes - Anand Patwardhan; Sabine Bardin; Stéphanie Miserey-Lenkei; Lionel Larue; Bruno Goud; Graça Raposo; Cédric Delevoye (Nature Communications, 2017)
The anterograde movement of Golgi-derived vesicles requires the small GTPase RAB6, while its effector ELKS targets these vesicles to particular areas of the plasma membrane. Here the authors show that RAB6 and ELKS function in the biogenesis of melanosome, demonstrating that the secretory pathway can be directed towards intracellular organelles of endosomal origin.